Competitiveness, economic growth and human development in Latin American and Caribbean countries 2006-2015: A performance and correlation analysis (2019)
Purpose: The purpose of this paper is to analyze the performance and the relationship between competitiveness, real gross domestic product (GDP) growth and human development in 20 countries of the Latin America and Caribbean region during the 2006-2015 period. The main argument to uphold here is that – from the perspective of virtuous circle – countries with better conditions of competitiveness are those with better economic performance and with better conditions for human development. Design/methodology/approach: Time series data were organized at three levels: individual countries, groups of nations and Latin America and Caribbean as a whole. Indicators used were: index of competitiveness, rates of change in real GDP and Human Development Index. Cluster analysis tests were performed: data ranges were determined and quintiles were established. Countries were ranked in five categories and comparative position matrices were determined for each variable. Linear correlations between indexes were calculated. Linear correlation coefficients were determined in terms of groups of countries and considering Latin America and Caribbean as a whole. Findings: Findings revealed that decreasing conditions in competitiveness and economic growth indicators are the representative situation since 2009. The most competitive country in the region is Chile, and the weakest is Venezuela. Nevertheless, all Latin American and Caribbean countries analyzed seem to have made progress in terms of human, economic and social development. Regarding correlations, Dominican Republic showed an inverse relationship between competitiveness and economic growth, while Jamaica and Venezuela showed inverse relationships between competitiveness and human development. At the individual country level, no statistically significant relationship between economic growth and human development was detected. Research limitations/implications: Findings highlight the necessity of future research that result in a deeper understanding of the transmission mechanisms between economic and social performance in Latin American and Caribbean countries. Particular reasons at the micro level that explain improvements or deteriorations in competitiveness and human development must also be analyzed. Based on the degrees of freedom, time series could have included more years, but a lack of information was found for some countries. It would also be necessary to observe each particular case considering the type of economy, production characteristics and export/import composition. Practical implications: Results complement the existing literature by exploring competitiveness and its relationship with economic and social variables in developing countries. The authors also believe that this paper is relevant for macroeconomic and social policy debates involving competitiveness and human well-being in this region of the world. Originality/value: This paper supports an important argument: human well-being and national development must be the ultimate goal of competitiveness. Traditional literature focuses on levels and determinants of competitiveness in developed countries, but it usually does not take into account social and human aspects of the process in developing countries. Little attention has been paid to analyze the relationship between competitiveness and socioeconomic variables in developing countries. Methods and findings of this paper complement the existing literature by studying the relationships among competitiveness, real GDP growth and human development in Latin American and Caribbean countries, using correlation analysis. © 2019, Emerald Publishing Limited.